Les capitales des cités gauloises, simulacra Romae ? - Michel Reddé (Gallia)
Does the classic notion of the Mediterranean town, the model of urbanism for the new civitas-capitals founded by Rome in the provinces after the Conquest, respond to an archaeological reality or is it an ‘‘Idealtyp’’? The archaeological inquiry presented here shows that, at least in Gallia Comata, the rise of new civitas-capitals is not an uniform phenomenon and that several factors played a decisive part in this process: the Protohistoric legacy, which needs to be profoundly re-evaluated in relation to our traditional vision, the dynamic relating to urban development prior to the Conquest, the place of large late Iron Age sanctuaries, the establishment of the new road network which altered the earlier geographical and economic balance, the involvement of local elites, their degree of integration into the new Roman political structures and their wealth which determined their capacity for euergetism. Of course, the regional differences can be very pronounced and the ex nihilo foundation of a provincial capital, designed as such from the beginning (Cologne) cannot be compared to the foundation of a civitas peregrina such as Le Mans. The chronological process itself seems quite slow and gradual, even in the case of new cities like Amiens or Autun, often passing through several successive stages. With some noteworthy exceptions, most of Gallia Comata’s capitals do not seem to witness significant changes before the last decade BC, sometimes much later, and the urbanization process often lasts at least until the middle of the 1st c. AD, sometimes up to the Flavian period.